Specifications of the clinical stabilometry platform ‘ADAP_NORMES13’ - Gagey, Pierre-Marie (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Latin posturologists unanimously recognize and accept that the normalization of stabilometry can only be based on decisions often arbitrary . These specifications of the standard stabilometry platform, ADAP-Normes2013, represent the first series of those decisions, admittedly arbitrary but made after a discussion with the French and Russian platform manufacturers, in Paris on 13 December 2007.